INVESTIGATING FORMULAIC EXPRESSION TO IMPROVE STUDENTS SPEAKING SKILL - Halimatus Sa'adah; Erma Yuli Setyaningrum; Yunita Ayu Riski; Nur Afifi (Institut Pendidikan Tapanuli Selatan, 2024)
This study discusses about the use of formulaic expressions in English Language Teaching (ELT) and the impact on students' speaking skills especially speaking skill. This study used a descriptive qualitative research study conducted at MA Mambaul Hisan to investigate the use of formulaic expressions employed by an English teacher and students when conducting English language teaching in the classroom. The research utilized observation as the primary research instrument, with an observation sheet used for data analysis. The participants included 22 eleventh-grade students. The researchers recorded and analyzed the conversations between the teacher and students during learning activities and conducted an interview with the teacher with findings the dominance of collocations and inserts used in the class. The results suggest that formulaic expressions improve students' communicative abilities and language comprehension